Sustainability as a success factor for tourism destinations: a systematic literature review - Santos, Margarida Custódio (2022)
Purpose This study sought to assess the extent to which tourism research has considered sustainability as a success factor for tourism destinations. It also aims to identify the relevance of the economic, environmental and socio-cultural dimensions of sustainability for tourist destination success, identify gaps in the literature and draw theoretical and practical implications and make recommendations. Design/methodology/approach The research methodology consists of a systematic literature review on sustainability as a success factor for tourism destinations. Findings Research interest in the topic is recent and mostly focused on environmental sustainability. Developing a sustainable tourism policy and performing adequate destination management are crucial for tourism destination success. It is also acknowledged that perceiving a destination as sustainable has a significant positive impact on tourists' experiences, purchasing behaviour and loyalty. Originality/value This study's value arises from the fact that, to the best of the authors' knowledge, no systematic literature review was yet been performed on the topic of sustainability as a success factor for tourism destinations.